2015
DOI: 10.1136/thoraxjnl-2015-206998
|View full text |Cite
|
Sign up to set email alerts
|

Long-term lung function in postinfectious bronchiolitis obliterans

Abstract: We read with great interest the paper by Colom et al 1 on pulmonary function of a paediatric cohort of patients with postinfectious bronchiolitis obliterans (BO). The authors concluded that pulmonary function remained severely impaired, showing an obstructive pattern with air trapping that slowly improved during childhood. In addition, they showed that nine (19%) patients developed thoracic deformity and seven (15.2%) bronchiectasis. On the first view, contrary to their findings, the FVC and FEV 1 increased by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 1 publication
1
7
0
1
Order By: Relevance
“…Clinical improvement during the disease process is somewhat attributed to the growth of the lungs and probably does not indicate regression of the pathology in the small airways [12,13]. In the majority of the published cohort studies, the overall prognosis of pulmonary function is poor.…”
Section: Introductionmentioning
confidence: 97%
“…Clinical improvement during the disease process is somewhat attributed to the growth of the lungs and probably does not indicate regression of the pathology in the small airways [12,13]. In the majority of the published cohort studies, the overall prognosis of pulmonary function is poor.…”
Section: Introductionmentioning
confidence: 97%
“…(11) The bronchodilator test turned out positive in all cytological patterns, including the exclusively neutrophilic one, corroborating studies with long-term follow-up of patients with PIBO. (12,13) Those studies have shown severe and permanent impairment of lung function, though air trapping slowly decreased with patient growth. (1,12,13) There were no significant correlations between sputum cellularity and the clinical, functional, and CT variables studied.…”
Section: Dear Editormentioning
confidence: 99%
“…(12,13) Those studies have shown severe and permanent impairment of lung function, though air trapping slowly decreased with patient growth. (1,12,13) There were no significant correlations between sputum cellularity and the clinical, functional, and CT variables studied. The lack of statistical correlation between the variables in the present study was probably due to the small sample size; the low prevalence of the disease represents an analytical challenge.…”
Section: Dear Editormentioning
confidence: 99%
“…Le point de départ est une infection virale, et les nourrissons sont les plus vulnérables. A moyen terme, ces patients gardent une altération de leur fonction respiratoire avec un syndrome obstructif sur les petites voies aériennes, une distension thoracique parfois importante, des anomalies de ventilation sans anomalies de perfusion, et une réponse aux beta-2 variable [41,42]. Certains restent symptomatiques et entrent dans la définition de la BPCO de l'adulte avec une évolution vers l'insuffisance respiratoire chronique.…”
Section: Les Bronchiolites Oblitérantes Post-viralesunclassified